Perpaduan Nada‐nada dalam Perspektif Harmoni dan Aplikasinya Terhadap Mahasiswa - V. Yoni Kaestri (Institut Seni Indonesia Yogyakarta, 2015)
The combination of tones in the diatonic musical study is called the harmony. Harmony here is intended for the human voice, that encompasses the soprano (S) for high female voice, the alto (A) for low female voice, the tenor (T) for high male voice, and the bass (B) for low male voice. Each sound has a different register, as it was introduced at the beginning part of many harmony text books, for example the one that was written by Gustav Strube. The initial step of tonesarrangements is based on the tonic, dominant, and sub‐dominant chords. Because the triad chord is consists of 3 notes only while the four voices are needed in the SATB arrangement, doubling the one of triad components is necessary. In addition to doubling treatment we should be aware of applying the proper chord positions, whether it is the basic position (bass doubling), the first inversion (soprano doubling), or the second inversion (bass doubling). In the fourth voices chord, eg the dominant seventh chords, although it is possible to treat the doubling by eliminating the element of its tone composite, it is not usually applied due to the number of its chord tones is already four. While in its application to the student, it is better to be based on the memorization of basic chords, for example major, minor, diminished, and augmented chords, after that continued by working on the triad chord, four voice chords, and also the neapolitan sixth.